Exploring EFL Learners Students-Teacher Relatedness - Al Fatih, Ahmad Fiqi; Lestari, Lies Amin; Anam, Syafi'ul (Jurnal Pendidikan Indonesia, 2024)
Purpose this study of to know how students’ and teacher views on students and teacher relatedness in the classroom related to vocabulary learning. Specifically, the methodology used in this research was giving the researcher ability to explore students and teacher point of view on the relatedness between them inside and outside classroom. Thus, qualitative research methodology is going to be utilized to achieve the research objective. The subjects of the study were one senior high school EFL teacher, and the students of one class of English language major class consisting of 4 students. The data of this research was obtained using interview questions instrument. The scope of this study is to explore students-teacher relatedness inside or outside the classroom. However, the results of this study might not be able to be generalized. SDT believe parents also has playing role in learners’ success in learning, meanwhile, this research is only focuses on the relatedness between students-teacher. In addition, it would be inconvenient to do research on every parents. The results of this study are expected to give beneficial information for other researcher who conduct study on this similar topic. The results of this study are expected to give beneficial information for the teacher which may giving better attention in the learners learning process by providing support in every chance they have. To the curriculum designer what is learners needs when they conduct vocabulary learning.